Combined chemoimmunotherapy of patients with mature B-cell non-Hodgkin lymphomas age group until 18 years: results of multicenter study NHL 2004 m with rituximab and modified B-NHL BFM 90 protocol applications - E. V. Samochatova; L. N. Schelikhova; M. B. Belogurova; A. V. Schamardina; E. V. Bascharova; D. V. Litvinov; N. V. Myakova; L. G. Fechina; O. P. Chlebnikova; E. V. Inuschkina; O. V. Riskal; P. Z. Schammasov; et al. (Онкогематология)
Therapy results of 61 patients (children and adolescents, 2—17 years of age; a median — 8.76 years) with B-cells non-Hodgkin lymphomas III—IV stage and B-cell acute leukemia (B-NHL/B-ALL), treating according to protocol with polichemotherapy and monoclonal antibodies against B-cell receptor CD20 — rituximab (Mabthera, Hoffmann La Roche) applications, are presented. The protocol consist of cytoreductive phase and 6 polychemotherapy courses, similar to original protocol B-NHL-BFM 90, with exception of decreasing methotrexate dosage in 2 first courses from 5 to 1 g/m2/24 hours. Rituximab — 375 mg/m2 IV — in Day 0 first 4 courses was given.Four patients have died within first 3 weeks of therapy, 2 were primary refractory patients and 55 patients have achieved complete remissions. There was no case of remission death; relapse has developed only at one patient (neuroleukemia in patient with Burkitt lymphoma). 54 patients (88%) are in continuous complete remission. Overall and event-free survival rate were 0,90±0,04 with median follow-up after therapy ending 34 months (12—53 months). Authors discuss tactics of such combined therapy, features of remission registration, considering that at third of patients, residual mass was long-term detected, and for which assessment besides CT/MRT a positron-emission tomography (PET) and/or a repeated biopsy were done. Also it is possible to conclude that with use of target therapy chemotherapy intensity of such tumors can be reduced. Authors concluded that in cases of target therapy efficacy criteria should be modified, and it is necessary to use as much as possible informative technique to remission control (PET, minimal residual disease assessment with use of molecular-genetic methods).